Studi Literatur Representasi Risiko Infeksi Kulit dalam Diskursus Media Sosial tentang Thrifting di kalangan Gen Z - Shiba, Aisha Arifah (Jurnal Ners, 2025)
The growing popularity of thrifting among Generation Z has transformed this practice into a prominent form of digital consumption, yet it has simultaneously generated extensive discourse regarding the risk of skin infections associated with second-hand clothing. This study aims to identify and analyze how skin infection risks are represented in scientific literature and constructed within social media environments. A Systematic Literature Review (SLR) guided by PRISMA was conducted by examining studies published between 2016 and 2025 across multiple academic databases. From an initial pool of 326 records, 19 articles met the inclusion criteria and were analyzed thematically. The findings reveal that biological risks such as bacterial, fungal, and parasitic contamination are consistently reported in microbiological studies on second-hand clothing. Meanwhile, risk perceptions on social media are shaped through visual narratives, user experiences, and algorithmic amplification, resulting in multilayered and emotional representations that do not always align with empirical evidence. The discussion emphasizes that the interplay between scientific findings and digital discourses produces a complex construction of risk within thrifting practices. In conclusion, the representation of skin infection risks in thrifting is a multidimensional construct influenced by scientific data, social perceptions, and digital communication patterns among Generation Z.